Neurocirculatory asthenia and mitral valve prolapse syndrome from a psychopathological perspective - Łukasz Grabowski (Family Medicine & Primary Care Review)
The article focuses on a review of clinical information on psychocardiac disorders, such as neurocirculatory asthenia (Da Costa’s syndrome, NA) and mitral valve prolapse syndrome (MVPS). NA is a disease which manifests mostly in respiratory and cardiovascular systems, while MVPS is characterized by the disturbed displacement of an abnormally thickened and superfluous mitral valve to the left atrium over the systole. The general theoretical division of psychosomatic disorders into functional disorders (somatoforms) and neurovegetative dysfunctions have been discussed. Symptoms of NA (palpitations, shortness of breath, pain, rapid pulse, digestive disorders, giddiness, sleep disturbances, headache) and MVPS (autonomic system dysfunction, often chest pain, orthostasis, palpitation, dyspnea on exertion, anxiety) were given and summarized. Accompanying psychopathological ailments have been indicated (especially falling within the scope of anxiety and similar psychological phenomena). Finally, the effects of β-adrenoceptor blocking drugs (beta-blockers) and psychotherapy on the course of psychopathological symptoms in NA and MVPS were briefly discussed. Psychocardiac disorders are a heterogeneous group of diseases which require a complex differential diagnosis, both physical and psychopathological. The most common psychological problems in NA and MVPS are anxiety disorders, and they should be corrected pharmacologically and by adequate psychotherapy. However, observation of the somatic state of patients ought to be regular.